Prevalence of intestinal parasitic infections in cases of diarrhoea among school children attending a tertiary care hospital: a two year study - Tenali, Ravi Kumar; Badri, Naveen Kumar; Kandati, Jithendra; Ponugoti, Munilakshmi (International Journal of Contemporary Pediatrics, 2018)
Background: Globally every year 1.7 billion cases of diarrhoea are registered as per the WHO report 2017. Intestinal parasitic infections [IPI] are one of the top ten major public health problems in developing countries with an estimated prevalence of 30-60% in developing countries compared to 3% in developed countries. School age children are the common vulnerable group with the highest prevalence and infection intensities. The objective of the present study is to study the prevalence of parasitic infections in school children as a causative factor for diarrhoea and associated risk factors involved with relation to their hygiene and socio demographic characters. Methods: A cross sectional study was conducted for a period of two years from January 2015 to December 2016 and stool specimens from the children aged 5-18 years suffering from diarrhoea were screened for parasitic infections following standard guidelines and as per the ethical committee guidelines. The socio demographic characters, risk factors and hygienic characters of the cases were noted from the parents or guardians or children in a separate predesigned questionnaire sheet. Data was analyzed using SPSS software version 13 and P value<0.05 was considered significant. Results: T The prevalence of parasitic infections in the Present study was 22.95% and males were more common. 8-11 years was the most common age group and mean age was 11.6±1.8 years. Statistically significant association was found with hand washing before meals, socio economic status, and method of hand washing after defecation. Entamoeba histolytica was the major parasitic pathogen followed by Ascaris lumbricoides. Other parasites were Giardia lamblia, Ancylostoma duodenale, Cryptosporidium, Isospora, Enterobius and Trichuris trichura. Conclusions: There is lack of awareness regarding dog bite and its management among the rural population.